POWER FORCES WITH VARIABLE APPLICATION POINT - V. V. Permyakova (Научный вестник МГТУ ГА, 2016)
The article shows algorithm of solving problems in calculating work of force applied to the floating point in a solid. A theorem proof is provided calculating power of such a force. The use of the theorem and its consequence is shown on some examples.